Factors Affecting Generation Y in Making the Purchase Decision of Healthy Fast Food in Klang Valley of Malaysia - Kang, Kai (2014)
The fast food industry is in an upward trend. The demand for fast food product is now growing as it is convenience which suits the lifestyle of customers. With the changing lifestyle of Malaysian consumers, more people tend to eat outside especially for fast food. Along with the fierce competition among different fast food companies, customers has variety choice of fast food pattern and restaurants. Therefore, how companies become innovative and get prepared to change accordingly based on the changing of eating habit to avoid from losing their existing and future potential customers is supposed to be an issue faced by the managers of fast food restaurant. There are more than 3, 000 fast food restaurants in Malaysia market and fast food is the most popular food especially for young generations. One of the reason is that young people is the prime target of fast food advertising. According to the literatures, it can be seen that Generation Y order more fast food than other age groups during the meal time. However, most of fast food served is perceived by the consumers as deep fried in partially hydrogenated oils. This oil is also known as trans-fats that will lead to heart diseases and high cholesterol rates. Moreover, fast food contains a lot of chemical additives and it also lacks accurate nutrition. Based on previous study, fast food can cause some problems like obesity and influence young people’s health. In Malaysia, the government is concerned about the obesity issue and some measures have been taken to avoid this happening especially among young generation. Meanwhile, young generation have perceived it and changed the eating habit to pursue the healthy fast food. So in order to investigate the factors which will influence the purchasing intention of choosing healthy fast food among Generation Y, the author developed a research framework to identify the relationship between attitudes, subjective norm and some other elements towards behavior intention, which is based on the theoretical framework of the theory of reasoned action and developed further. This study adopts a cross-sectional survey design because this study makes inferences about a population of interest at one point in time. Questionnaires will be distributed to the diners who belongs to Generation Y in fast food outlets in Klang Valley and 384 respondents are included. A descriptive analysis will show the respondents profile and reliability test will make sure that all the data collected are reliable. And multiple regressions will be used to identify the relationship between independent variables and dependent variable. This research confirms that all five independent variables except price promotion have the positive influence on young generation’s purchase intention of healthy fast food. The possible reason for the not significant relationship between price promotion and behavior intention will be given. Recommendations and discussions for future studies are also provided.